Equiconvergence in summation associated with elliptic polinomial - Fargana, A; Rakhimov, Abdumalik; Khan, Ahsan Ali; Hassan, Torla (Kulliyyah of Engineering International Islamic University Malaysia (IIUM), 2017)
We compare the Fourier integral with the Fourier series in summation associated with elliptic polinomial.